The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1124/mol.113.086496
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor–Mediated Downregulation of Brainstem K+–Cl Cotransporter and Cell-Type–Specific GABA Impairment for Activation of Descending Pain Facilitation

Abstract: Chronic pain is thought to be partly caused by a loss of GABAergic inhibition and resultant neuronal hyperactivation in the central pain-modulating system, but the underlying mechanisms for pain-modulating neurons in the brain are unclear. In this study, we investigated the cellular mechanisms for activation of brainstem descending pain facilitation in rats under persistent pain conditions. In the nucleus raphe magnus (NRM), a critical relay in the brain's descending pain-modulating system, persistent inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 39 publications
(66 reference statements)
2
51
0
Order By: Relevance
“…Opioid-induced inhibition of GABA release disinhibits PAG and RVM output neurons (Heinricher and Ingram, 2008;Lau and Vaughan, 2014) and microinjection of GABA A receptor antagonists in either area results in antinociception (Moreau and Fields, 1986;Heinricher and Tortorici, 1994;Bobeck et al, 2009). Altered GABA release in the PAG and RVM is associated with chronic inflammatory or neuropathic pain models, although both increases and decreases in GABAergic mIPSCs have been reported (Hahm et al, 2011;Zhang et al, 2013) indicating the complexity of the changes in the descending pain circuit. One key variable in these studies may be age of animals that are used for recording as we have previously reported a marked decrease in GABA release probability between neonatal and adult RVM neurons that is the result of increased endocannabinoid tone in the adult rat RVM (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid-induced inhibition of GABA release disinhibits PAG and RVM output neurons (Heinricher and Ingram, 2008;Lau and Vaughan, 2014) and microinjection of GABA A receptor antagonists in either area results in antinociception (Moreau and Fields, 1986;Heinricher and Tortorici, 1994;Bobeck et al, 2009). Altered GABA release in the PAG and RVM is associated with chronic inflammatory or neuropathic pain models, although both increases and decreases in GABAergic mIPSCs have been reported (Hahm et al, 2011;Zhang et al, 2013) indicating the complexity of the changes in the descending pain circuit. One key variable in these studies may be age of animals that are used for recording as we have previously reported a marked decrease in GABA release probability between neonatal and adult RVM neurons that is the result of increased endocannabinoid tone in the adult rat RVM (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…RVM slice preparation was performed as described previously (Li et al, 2015). Rats were deeply anesthetized with isoflurane and the brains were rapidly removed and placed in N-methyl-D-glucamine-sucrose-based "cutting buffer" containing the following (in mM): 52 N-methyl-D-glucamine, 2.5 KCl, 0.5 CaCl 2 , 10 MgSO 4 , 1.2 NaH 2 PO 4 , 30 NaHCO 3 , 25 D-dextrose, 75 sucrose, 5 sodium ascorbate, 2 thiourea, 3 sodium pyruvate, pH 7.4, adjusted with HCl and 300 -310 mOsm (Zhao et al, 2011;Ting et al, 2014). Coronal slices (180 -200 m) were cut in 95% O 2 -and 5% CO 2 -oxygenated cutting buffer.…”
Section: Methodsmentioning
confidence: 99%
“…All NRM microinjection sites were verified histologically after the experiment by injection of 0.5 l of a blue dye, and controls of off-site injections were performed as described elsewhere (36). The confined effect of an injected drug within the NRM with this microinjection method has been demonstrated in previous studies (21,33,34). The pain threshold was measured every 5 min by paw withdrawal test on a freely moving rat using a Hargreaves analgesia instrument (Stoelting, Wood Dale, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Synaptosome Preparations and Western Blot Analysis-The synaptosome preparations and Western blot analysis were performed as described in previous reports (21,38). For synaptosome preparations, NRM tissues from saline-and CFA-injected rats were homogenized gently in ice-cold 0.32 M sucrose buffer at pH 7.4 and then centrifuged for 10 min at 1000 ϫ g (4°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation